El chaccu de la comunidad campesina cahuide - sector pueblo jesús como un atractivo impulsor del turismo vivencial en la provincia de santiago de chuco - Villegas Diestra, Olinda Elizabeth (2015)
This thesis called, The Peasant Community Chaccu Cahuide - people Jesus sector as a driver of experiential tourism attraction in the province of Santiago de Chuco, aims to determine the qualities of an attractive chaccu driver of development in Living Tourism Jesus Cahuide- farming community village in the province of Santiago de Chuco sector. This work was developed in the Rural Community Cahuide - people Jesus sector for housing within a species of South American camelids such as vicuna valuable species for having the finest fiber and high calorific grade, second stage of the mountains of the Freedom in the presence of one species of South American camelid vicunas are a valuable species for having the finest fiber and high heating degree that makes possible the realization of chaccu. Similarly it is found • that the hypotheses such as the development of this event that has been held annually every year in the same place and met a rising demand; Community involvement is befare, during and after the event which divided the tasks involved in various activities such as rodeo, shearing, safety, guidance, etc. And the board assumes responsibility for the realization of chaccu because they are directing and running the event and be considered a tourist attraction for the development of experiential tourism in this area called people Jesus of the rural community Cahuide is a remate area, free naturallandscape with the presence of ichu or straw Puna which gives prominence to the event increasing its attractiveness for future visitors looking to escape the routine nature and thus promote experiential tourism in the province of Santiago de Chuco . Finally, we worked with a methodology' like these methods; Ethnographic what was used at the stage of field to know the qualities of chaccu to consider it an attractive driver of experiential tourism in the rural community Cahuide, the analytic-synthetic was used at the stage of Cabinet to identify the qualities regarding the attitude community, access to the event, natural attractiveness, the structuralistfunctionalist was used to determine and describe the functions of the mahagement structure of the rural community Jesus Cahuide -industry people to develop experiential tourism in the province of Santiago de Chuco.